Distributing Philanthropic Funds to Indonesian Muslims amid the Pandemic through a Maṣlaḥah view: Weaving Social Safety Nets or Fortifying the Healthcare System? - Khasanah, Karimatul; Ansori; Sobirin, Mohamad (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2023)
The COVID-19 pandemic has exerted profound effects on the socio-economic landscape of the Indonesian populace, giving rise to vulnerable social segments. Throughout this period, BAZNAS, LAZISNU, and LAZISMU have overseen and allocated philanthropic resources from the Indonesian Muslim community for the mitigation of COVID-19-related challenges. The objective of this study is to address the inquiry regarding the allocation of funds for managing COVID-19 through a maṣlaḥah perspective, utilizing data sourced from documents of the three Amil institutions and insights gathered from interviews. The investigation reveals a congruence between BAZNAS and LAZISNU in their fund distribution practices, both demonstrating a concerted endeavor to leverage Islamic philanthropy for the establishment of social networks. Conversely, LAZISMU places greater emphasis on establishing a social health system amidst the pandemic, as evidenced by health programs being accorded second priority after social humanitarian initiatives. Nevertheless, a comprehensive conclusion may be drawn that all three institutions prioritize health and humanitarian concerns as focal points in the distribution of zakat, infaq, and alms within the context of the pandemic. From the standpoint of the maṣlaḥah theory, the prioritization rationale indicates that the allocation of Zakat, Infaq, and Alms funds is predominantly rooted in maṣlaḥah 'urfiyyah (or maṣlaḥah mulghah ghair mu'tabarah) rather than maṣlaḥah syar'iyyah.